1971
DOI: 10.1111/j.1471-0528.1971.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Phaeochromocytoma of the Ovary

Abstract: AND SummaryA case of phaeochromocytoma of the ovary simulating pre-eclamptic toxaemia of pregnancy in a 15-year-old girl is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Hayashi et al have reported a case of small cell carcinoma of the vagina in a 91-year-old woman (8). Ovarian and uterine paragangliomas are equally rare as those arising in the vagina (9)(10)(11)(12)(13)(14). The current case is the fourth paraganglioma to be described in the vagina (2)(3)(4).…”
Section: Fig 2 Amentioning
confidence: 99%
“…Hayashi et al have reported a case of small cell carcinoma of the vagina in a 91-year-old woman (8). Ovarian and uterine paragangliomas are equally rare as those arising in the vagina (9)(10)(11)(12)(13)(14). The current case is the fourth paraganglioma to be described in the vagina (2)(3)(4).…”
Section: Fig 2 Amentioning
confidence: 99%
“…One case has been excluded as describing a case of peritoneal carcinomatosis from extra‐adrenal paraganglioma in a male patient . Therefore, the studies included in this review are eight published in peer‐reviewed journals . Table shows the clinical characteristics of published cases of OP.…”
Section: Resultsmentioning
confidence: 99%
“…Although they have been described in the vagina, uterus, and vulva, 1-3 their exact incidence is uncertain. In the 5 reported ovarian cases, 4,5,8 the age of presentation was variable, ranging from the young 4 to postmenopausal patients. 6 All reported cases were of sporadic type and in only one instance bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…3 In the ovary, only 5 cases have been reported. 4-6 These tumors are often associated with clinical hypertension and usually follow a benign course. Immunohistochemically, they have a well-established phenotype.…”
Section: Introductionmentioning
confidence: 99%